2018
DOI: 10.1038/s41598-018-20994-x
|View full text |Cite
|
Sign up to set email alerts
|

Receptor for advanced glycation end-products and ARDS prediction: a multicentre observational study

Abstract: Acute respiratory distress syndrome (ARDS) prediction remains challenging despite available clinical scores. To assess soluble receptor for advanced glycation end-products (sRAGE), a marker of lung epithelial injury, as a predictor of ARDS in a high-risk population, adult patients with at least one ARDS risk factor upon admission to participating intensive care units (ICUs) were enrolled in a multicentre, prospective study between June 2014 and January 2015. Plasma sRAGE and endogenous secretory RAGE (esRAGE) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 50 publications
3
49
0
Order By: Relevance
“…This is a secondary analysis of a prospective multicentre observational study. Data used in this ancillary study were prospectively obtained from patients previously enrolled in a large multicentre observational study of the predictive values of RAGE (the receptor for advanced glycation end‐products) isoforms and gene variants for the onset of ARDS (PrediRAGE study) . Between June 2014 and January 2015, 500 critically ill adult patients in whom at least one ARDS risk factor was identified were enrolled.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a secondary analysis of a prospective multicentre observational study. Data used in this ancillary study were prospectively obtained from patients previously enrolled in a large multicentre observational study of the predictive values of RAGE (the receptor for advanced glycation end‐products) isoforms and gene variants for the onset of ARDS (PrediRAGE study) . Between June 2014 and January 2015, 500 critically ill adult patients in whom at least one ARDS risk factor was identified were enrolled.…”
Section: Methodsmentioning
confidence: 99%
“…Because most patients with ARDS are identified within 7 days of recognition of the underlying risk factor(s), we postulated that ΔP could be a risk predictor for ARDS development in patients without ARDS but with at least one ARDS risk factor upon admission to the intensive care unit (ICU). To assess this association, we did a secondary analysis of individual patient data that were prospectively obtained during a large multicentre observational study …”
Section: Introductionmentioning
confidence: 99%
“…Data used in this ancillary study were prospectively obtained from patients previously enrolled in a large multicenter observational study on the predictive values of RAGE isoforms and gene variants for the onset of ARDS (PrediRAGE study, clinicaltrials.gov identifier: NCT02070536 ) [ 28 ]. Between June 2014 and January 2015, 500 critically ill adult patients admitted to five intensive care units (ICUs) were enrolled in the primary study if they had at least one ARDS risk factor [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, respiratory conditions did not improve after rTM in the patients who died. Recently, Jabaudon et al reported that a higher baseline level of sRAGE was associated with development of ARDS [22]. In this study, on day X (just before administration of rTM), the plasma concentrations of sRAGE in patients 5 and 6, who later died, were 4715 and 8501 pg/mL, respectively, whereas the median concentration of sRAGE in the patients who survived was 1817 [IQR 1437-1904] pg/m.…”
Section: Discussionmentioning
confidence: 48%